The preparation of hollow Fe3O4/Pd@C NCs to stabilize subminiature Pd nanoparticles for the reduction of 4-nitrophenol. (5th March 2020) - Wang, Congcong; Chen, Yixin; Feng, Siyang; Zhang, Nan; Shen, Lin; Zhang, Kai; Yang, Bai
Abstract : Hollow Fe3 O4 /Pd@C NCs to stabilize subminiature Pd nanoparticles and exhibit excellent performance in the reduction of 4-NP. Abstract : N-Doped hollow Fe3 O4 /Pd@C nanocontainer (NC) composites, involving the loading of magnetic Fe3 O4 and subminiature noble metal Pd nanoparticles (NPs), were prepared. The synthetic process involves the decomposition of Fe3 O4 /Pd 2+ @ZIF-8 and the polymerization of dopamine simultaneously via a "Chelation Competition Induced Polymerization" process, forming hollow polymer NCs. Then, they were carbonized into Fe3 O4 /Pd@C NCs. The structure and composition of the as-prepared nanocontainers were characterized. The catalytic performance of the Fe3 O4 /Pd@C NC composites was studied by the reduction of 4-nitrophenol with NaBH4 as a reducing agent. The reaction rate constant was calculated according to the pseudo-first-order reaction equation. It was found that subminiature Pd NPs were obtained, and the coordination interaction between Pd and N in PDA prevented Pd NPs from aggregating during high-temperature calcination, resulting in a high k value. Besides the good catalytic properties, high stability of Fe3 O4 /Pd@C NCs was also confirmed.